The Influence of Online Shopping Convenience and Shopee Live on Purchase Decisions through Consumptive Behavior of Generation Z Students at Universitas Negeri Jakarta - Syifa Aulia Azzahra; Afidah Nur Aslamah, M.Si; Dr. Osly Usman, M.Bus; Dr. Ryna Parlyna, M.B.A (Journal of Digital Business and Global Economy, 2025)
This research is conducted to examine the influence of Online Shopping and Shopee Live on Purchase Decision through Consumptive Behavior among Generation Z students at Jakarta State University. The rapid growth of e-commerce platforms accompanied by live streaming features has changed digital consumption patterns, especially among the younger generation who are known to be responsive to technology. This research adopts a quantitative method employing an explanatory research framework. The research sample involved Generation Z students who had shopped through Shopee and used the Shopee Live feature, determined selected through a purposive sampling technique based on specific research criteria. Data collection was carried out through data were collected using a Likert-scale questionnaire and further processed using SmartPLS to test the relationship between variables. This study is expected to clarify both direct and indirect relationships among the examined variables, including the mediating function of consumptive behavior. The results of the present study provide contributions to digital marketing literature and can be a reference for e-commerce players in designing relevant strategies for young digital consumers.